PERILAKU MASYARAKAT TERHADAP PENGELOLAAN SAMPAH RUMAH TANGGA DI DESA MEUNASAH ALUE IE PUTEH KABUPATEN ACEH UTARA - Bakhtiar Bakhtiar; Daniel Ginting; Evawani M Silitonga (STIKes Al-Insyirah Pekanbaru, 2022)
Garbage is a problem that has become a global issue because it has a fairly varied impact. One of the phenomenal waste problems is related to pollution, both soil, air and water pollution. Pollution occurs as a result of unmeasured human actions and tends to ignore its negative impacts. This study aims to analyze the behavior of the village community of Meunasah Alue Ie Puteh towards household waste management. This research is a quantitative research with cross sectional research design. namely research that studies the dynamics of the correlation between the dependent and independent factors with the method of approach, observation or data collection all at once. This research was conducted in Meunasah Alue Ie Puteh Village, Baktiya District, North Aceh Regency with the time of the study being conducted from April to May 2022. The sample in this study amounted to 81 respondents using purposive sampling technique. The results showed that there was an influence of knowledge, attitude, income and infrastructure with household waste management where the p-value <0.05, while education had no effect on waste management because the p-value 0.05. Knowledge most dominantly affects community waste management (t value = 3.708). One of the participations that can be involved and carried out by the community is through the development of a waste bank, which is a place for sorting and collecting waste that can be recycled or reused that has economic value.